Pengaruh Foreign Ownership terhadap Transfer Pricing dengan Implikasi terhadap Tax Avoidance (LQ45 2018-2023) - Dessy Rosmawati; Debbie Christine (Politeknik Ganesha Medan, 2026)
This study uses a quantitative approach focusing on companies listed on the Indonesia Stock Exchange that are part of the LQ45 Index between 2018-2023. The sample selection uses purposive sampling. Data comes from secondary sources, found on idx.co.id. This study combines path analysis and panel data, testing using EViews 13. This study uses a robustness test to measure the robustness of the data from the research results. Structure I selected the Random Effect Model (REM), and structure II used the Common Effect Model (CEM). The results show that foreign ownership has a negative effect on transfer pricing, with a t-prob value of 0.0000 < 0.05 and a coefficient of -0.3788. Similarly, foreign ownership has a negative effect on tax avoidance, with a t-prob value of 0.0000 < 0.05 and a coefficient of -0.0255. However, transfer pricing has no effect on tax avoidance, as the t-prob. value of 0.2020 > 0.05. The Sobel test results show a value of 1.2476 < 1.96, indicating that transfer pricing does not act as a mediator between foreign ownership and tax avoidance. From a theoretical perspective, these results suggest that foreign ownership serves as a control mechanism that helps reduce aggressive transfer pricing for tax avoidance. The negative effect of transfer pricing on tax avoidance implies that transfer pricing policies are more related to operational efficiency than exploiting tax opportunities. The Sobel test results also support the idea that the relationship between foreign investors and tax authorities is not affected by transfer pricing policies.